Penggunaan Media Sosial Instagram sebagai Trend Media Dakwah - Erwan Efendi; Aura Jannah; Wahyu Hidayat; Wahyu Mulianto (VISA: Journal of Vision and Ideas, 2024)
The great influence of technological advances and the digital world has changed the way individuals access media and use social media to preach. Nowadays, it is difficult for people to resist the use of social media. On the other hand, in the midst of this epidemic, some people are addicted to preaching on social media. Da'wah is now delivered by media business people via the Zoom application, Google Meet, live streaming on Facebook, Instagram and YouTube, as well as WhatsApp groups.Because social media platforms such as Instagram can broadcast videos and photos online and allow permanent storage, they are often considered very effective tools for spreading Islamic principles. Without losing values, a short film lasting less than one minute without giving up the values ​​of preaching, Instagram is the most popular social media platform because its users don't get bored of looking for preaching information through Instagram. Because it is very easy for us to access this Instagram media to look for preaching news that is currently trending, besides that the preaching media via Instagram is currently very popular among millennials now, because it has become a booming trend among millennials.